Investigating the efficiency of student teachers’ self-recorded microlesson videos for initial teacher education at a university of technology in South Africa - Mollo, Paseka (Educational Challenges, 2025)
Many teacher training institutions now use micro-lessons to help student teachers develop specific competencies. These structured lessons allow future educators to practice their skills before entering real classrooms. Video-recorded micro-lessons have proven particularly effective in enhancing pedagogical abilities. Purpose. This research paper investigates the effectiveness of self-recorded micro-lesson videos in equipping prospective teachers for the challenges of actual classroom settings. The research gathers insights from student teachers’ reflective experiences, grounding its framework in Reflective Practice Theory. This model emphasises critical reflection on one’s teaching practices to foster growth and development. Methodology. This qualitative study involved 20 second-year Bachelor of Education students from the University of Technology, who were selected through purposive sampling to ensure a group rich in relevant experiences. Data collection was conducted through systematic observations and focus group interviews, which provided a multifaceted understanding of the participants’ experiences. These insights were analyzed using the Systematic Text Condensation (STC) method, allowing for a thorough examination of the students’ reflections and experiences. Results. Findings from the study illuminated the significant role that self-recorded micro-lesson videos play in enhancing student teachers’ reflective practices and lesson planning capabilities. By reviewing their recorded lessons, these student teachers could objectively evaluate their teaching performance and discern recurring patterns in their teaching strategies over time. This iterative viewing process not only allowed them to focus on specific teaching elements from classroom management to learner engagement but also fostered a deeper insight into student teachers’ perceptions of their teaching methods. Conclusion. As a result, this reflective approach not only empowers student teachers to refine their skills continually but also contributes to a comprehensive understanding of their teaching practices, ultimately enhancing their overall effectiveness as educators. The findings of this research carry important implications for teacher education programs, emphasizing that the integration of self-recorded micro-lesson videos could substantially enhance the professional development opportunities available to pre-service teachers, preparing them more effectively for their future careers in education.